RETRACTED: International experience in assessing the achievement of sustainable development goals in rural areas - Medvedeva Lyudmila; Zemlyakova Nataliya (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001